2016
DOI: 10.18632/oncotarget.10088
|View full text |Cite
|
Sign up to set email alerts
|

SPANXA suppresses EMT by inhibiting c-JUN/SNAI2 signaling in lung adenocarcinoma

Abstract: SPANXA (Sperm Protein Associated with the Nucleus on the X-chromosome, family members A1/A2) acts as a cancer-testis antigen expressed in normal testes, but dysregulated in various tumors. We found that SPANXA is highly expressed in low-invasive CL1-0 cells compared with isogenous high-invasive CL1-5 cells. SPANXA was preferably expressed in tumor tissues and associated with the prolonged survival of lung adenocarcinomas. SPANXA suppressed the invasion and metastasis of lung cancer cells in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…It has approximately caused 158000 deaths in the United States in the year 2015 [ 1 ]. Lung adenocarcinoma is the most common histological type of lung cancer, accounting for 50% of the incidences of non-small cell lung cancer (NSCLC) [ 2 ], and usually occurs in the glandular epithelium of the lung periphery from either type II pneumocytes or bronchioalveolar stem cells [ 3 ]. Lung adenocarcinoma is frequently diagnosed at advanced stages, contributing to a no more than 16% overall 5-year survival rate [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has approximately caused 158000 deaths in the United States in the year 2015 [ 1 ]. Lung adenocarcinoma is the most common histological type of lung cancer, accounting for 50% of the incidences of non-small cell lung cancer (NSCLC) [ 2 ], and usually occurs in the glandular epithelium of the lung periphery from either type II pneumocytes or bronchioalveolar stem cells [ 3 ]. Lung adenocarcinoma is frequently diagnosed at advanced stages, contributing to a no more than 16% overall 5-year survival rate [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that c-jun plays a positive regulatory role in EMT of various tumor cells, such as in lung cancer, breast cancer, and melanoma, and inhibits the expression of c-jun or its associated pathways to reduce tumor cell EMT. 17 20 Our results indicated that CNE-2R cells morphological characteristics altered from loose spindle cell structure to cell–cell adhesion of CNE-2 cells after c-jun silencing, and also this reversed the high expression of N-cadherin and low expression of E-cadherin in CNE-2R cells. These findings were consistent with a previous study by Ying et al, who demonstrated that c-jun knockdown in gastric cancer cells led to EMT reversion.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have shown that c-jun plays a positive regulatory role in EMT of various tumor cells, such as lung cancer, breast cancer, and melanoma, and further inhibits the expression of c-jun or its associated pathways to reduce tumor cell EMT. 17 20 But the effect of c-jun on EMT and cell migration of human NPC is rarely reported. In our previous work, CNE-2R cells were constructed by CNE-2 through intermittent high-dose γ-ray multiple irradiation, and we found that c-jun gene was highly expressed in CNE-2R cells compared with its expression in CNE-2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30], including the fostering of genome instability, a driver of cancer evolution (24). However, given that the normal function of many CT genes in spermatogenesis is unknown, it remained unclear whether proteins that normally specifically orchestrate meiotic chromosome segregation events (such as interhomolog association/recombination and sister centromere monopolarity) contribute to maintenance and/or development/progression of cancers.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%